A descriptive study on the difficulties encountered by left-handed clinicians at the University of the Philippines College of Dentistry, SY 2001-2002 - Lavarias, Arnel R.
Procedures in dental practice, whether it is oral prophylaxis, tooth restoration, or simple tooth extraction is equally difficult. Being left-handed or right-handed person, each poses differences and difficulties in accomplishing procedures. Their positions and positioning of the various dental instruments and equipment show the difficulty of each procedure. The aim of this study was to determine the difficulties encountered by left-handed dental operators in oral prophylaxis, tooth restoration and simple tooth extraction, relative to right-handed operators in UPCD through a questionnaire. Fifty-three (53) clinicians, whether left or right-handed, were included in the study. The left-handed respondents encountered difficulties in holding extraction forceps for posterior teeth and scaling the distal sites of tooth 18 and 28. For right-handed clinicians, the specific dental activities they encountered difficulties in were scaling in the distal sites of tooth 18, 28, and 48. Statistics show that there is significantly no difference in the difficulties encountered among left-handed and right-handed clinicians.